Pengaruh latihan interval dan latihan push-up terhadap daya tahan kardiovaskular dan kekuatan tubuh bagian atas pada remaja - Kornia, Muhammad Rizqi; Suyoko, Andri; Pranoto, Adi; Nugraha, Devid Prisma (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2025)
Adolescent physical fitness is a crucial determinant of health and long-term well-being, yet global data show that most adolescents fail to achieve recommended activity levels. This study aimed to evaluate the effectiveness of combining interval training with push-up exercises in enhancing specific components of physical fitness, namely cardiorespiratory endurance and upper body strength. A quasi-experimental one-group pretest–posttest design was employed with 29 adolescents who met predetermined inclusion criteria. Physical fitness was assessed using the 12-minute run test (Cooper test) to measure aerobic endurance and a 1-minute push-up test to assess upper-body muscular strength. Data analysis included parametric and non-parametric tests based on normality results. The findings demonstrated a significant increase in VO₂Max from 44.7 to 47.8 ml/kg/min (p = 0.002), alongside a meaningful improvement in push-up performance (p = 0.019). These outcomes confirm that the six-week intervention program effectively enhanced both aerobic endurance and muscular strength. The study concludes that interval training and push-ups, when combined, offer a practical, low-cost, and adaptable exercise model for adolescent fitness development. Beyond the statistical results, the contribution of this study lies in demonstrating how two simple training modalities can be systematically integrated to address key aspects of adolescent health and performance, with direct implications for school-based physical education and youth sports programs.